শামসুর রাহমানের শ্রেষ্ঠ কবিতা. - রাহমান, শামসুর 1929-2006. (ঢাকা : সাহিত্য প্রকাশ, 1999)
Selected poems by a 20th century Bengali author.
Poems.
Development Book Agency
In Bengali.
Keywords: Bengali poetry -- 20th century; Bengali poetry